2022
DOI: 10.1002/pam.22354
|View full text |Cite
|
Sign up to set email alerts
|

To What Extent Does In‐person Schooling Contribute to the Spread of Covid‐19? Evidence From Michigan and Washington

Abstract: In this paper we use data from Michigan and Washington on COVID case rates at the county level linked to information on the instructional modality offered by local public school districts during the 2020/2021 school year to assess the relationship between modality and COVID spread. We focus primarily on COVID case rates, but also provide estimates for hospitalizations (in Washington only) and deaths. District and month fixed effects models that exploit within‐district (over time) variation in instructional mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
19
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 40 publications
4
19
0
2
Order By: Relevance
“…As discussed in SI Appendix, our regression specification is motivated by a SIRD model, and the dependent variable in our analysis is case growth rates instead of new cases or hospitalizations. Consistent with Goldhaber et al (2021) and Harris, Ziedan, and Hassig (2021), our finding of a constant increase in growth rates implies a greater increase in cases in counties with more pre-existing cases.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…As discussed in SI Appendix, our regression specification is motivated by a SIRD model, and the dependent variable in our analysis is case growth rates instead of new cases or hospitalizations. Consistent with Goldhaber et al (2021) and Harris, Ziedan, and Hassig (2021), our finding of a constant increase in growth rates implies a greater increase in cases in counties with more pre-existing cases.…”
Section: Resultssupporting
confidence: 91%
“…Two closely related papers also examine the relationship between schools and countylevel COVID-19 outcomes in the US. Goldhaber et al (2021) examine the relationship between schooling and cases in counties in Washington and Michigan. They find that inperson schooling is only associated with increased cases in areas with high pre-existing COVID-19 cases.…”
Section: Resultsmentioning
confidence: 99%
“…Harris, Ziedan, and Hassig, 2021:26) concluded that their “results suggest that school reopenings have not increased COVID‐19 hospitalizations, especially for the 75 percent of counties that had the lowest baseline hospitalizations.” For the counties with the highest COVID‐19 hospitalizations at baseline, Harris, Ziedan, and Hassig, 2021:1) found that the “estimates are inconsistent across methods and are therefore inconclusive.” Goldhaber et al. (2020) examined data from Michigan and Washington state and found that in‐person schooling does not contribute to community transmission of the virus in locations with low levels of pre‐existing COVID‐19 cases.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For the counties with the highest COVID-19 hospitalizations at baseline, Harris, Ziedan, and Hassig, 2021:1) found that the "estimates are inconsistent across methods and are therefore inconclusive." Goldhaber et al (2020) examined data from Michigan and Washington state and found that in-person schooling does not contribute to community transmission of the virus in locations with low levels of pre-existing COVID-19 cases.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Transmission in schools is strongly influenced by disease incidence in the community, though clusters and outbreaks do occur in schools, camps, and sports settings - particularly when mitigation measures are not fully or consistently implemented. 22 , 23 , 24 , 25 , 26 …”
Section: Epidemiologymentioning
confidence: 99%